Advanced diagnostic genetic testing in inherited retinal disease: experience from a single tertiary referral centre in the UK National Health Service. Issue 1 (30th June 2016) - Khan, K.N.; Chana, R.; Ali, N.; Wright, G.; Webster, A.R.; Moore, A.T.; Michaelides, M.
Abstract : Abstract : In 2013, as part of our genetic investigation of patients with inherited retinal disease, we utilized multigene panel testing of 105 genes known to cause retinal disease in our patient cohorts. This test was performed in a UK National Health Service (NHS) accredited laboratory. The results of all multigene panel tests requested between 1.4.13 and 31.8.14 were retrospectively reviewed. All patients had been previously seen at Moorfields Eye Hospital, London, UK and diagnosed with an inherited retinal dystrophy after clinical examination and detailed retinal imaging. The results were categorized into three groups: (i) Testing helped establish a certain molecular diagnosis in 45 out of 115 (39%). Variants in USH2A ( n = 6) and RP1 ( n = 4) were most common. (ii) Definitive conclusions could not be drawn from molecular testing alone in 13 out of 115 (11%) as either insufficient pathogenic variants were discovered or those identified were not consistent with the phenotype. (iii) Testing did not identify any pathogenic variants responsible for the phenotype in 57 out of 115 (50%). Multigene panel testing performed in an NHS setting has enabled a molecular diagnosis to be confidently made in 40% of cases. Novel variants accounted for 38% of all identified variants. Detailed retinal phenotyping helped the interpretation of specific variants. Additional care needs to be taken when assessing polymorphisms in genes that have been infrequently associated with disease, as historical techniques were not as rigorous as contemporary ones. Future iterations of sequencing are likely to offer higher sensitivity, testing a broader range of genes, more rapidly and at a reduced cost.